MENTAL STRESS AMONG CIVIL ENGINEERING CONSTRUCTION SITE AGENTS AND FOREMEN IN THE NELSON MANDELA BAY METROPOLE - Erich HAYDAM; John SMALLWOOD (Journal of Construction Project Management and Innovation)
The construction industry as a whole has been suffering from mental stress due to a range of stressors imposed on the work force, resulting in behavioural habits which are not conducive to a healthy lifestyle, physical symptoms signalling burnout, chronic stress, and depression. An empirical study was conducted among medium to large civil engineering contractors in the Nelson Mandela Bay Metropole the sample stratum including site agents and foremen. The salient findings include: using unreliable and old tools, using dirty toilet facilites, and working on an untidy site are the most significant physical stressors; limited time spent with loved ones, tight deadlines, inadequate reward system, and work-life imbalance are the most significant organisational stressors; headaches, tense muscles, and smoking cigarettes are the most significant behavioural activities and physical sensations experienced;tired, weak and no energy, restless and on edge, and irritable are  the most significant sensations of stress; feeling sad or down, restlessness, and decrease / increase in appetite are the most significant symptoms of depression. The objective of the study was to ascertain what stressors are imposed on a sample of site agents and foremen in the civil engineering sector of the construction industry. Further to the aforementioned, the study intended to identify what forms of strain, as also, the degree of stress and depression experienced by the work force. It can be concluded that a vast array of stressors negatively affect the civil engineering sector of the construction industry. Subsequently resulting in stress, depression, and mental /physical strain.